Long term outcomes of surgical revascularization for isolated left main coronary artery stenosis: a single-center surveillance study - Yalçın Velibey; Eyup Tusun; Servet Altay; Nijat Nijat Bakshaliyev; Mehmet Karaca; Özge Güzelburç; Nihat Ozer; Mehmet Eren; Serap Aykut Aka; İbrahim Yekeler (KARE Publishing, 2015)
Objective: The objective of this study was to retrospectively analyze the clinical course and postoperative long-term survival of patients diagnosed with isolated left main coronary artery (LMCA) stenosis after surgical revascularization. Methods: A total of 38 patients (27 males, 11 females) who were diagnosed with isolated LMCA stenosis and underwent surgical revascularization were enrolled in the study. Isolated LMCA stenosis was classified into 2 groups: ostial stenosis and nonostial stenosis. Coronary events were defined as death of cardiac origin, the need for a new myocardial revascularization procedure, or the occurrence of myocardial infarction in the course of follow-up. The postoperative assessment period included short- and long-term follow-up. The study endpoint was defined as all-cause mortality. Results: Among the 38 patients who participated in the study, 25 suffered from ostial LMCA stenosis. The early postoperative mortality rate before hospital discharge was 2.6%. Median duration of postoperative long-term follow-up was 73.43 months (range: 0.17-187.23). Median duration of long-term follow-up free from coronary events or percutaneous coronary interventions was 73.43 months. Postoperative 2-year survival rate was 97.4%, and 5-year survival rate was 92.1%. The postoperative survival period and period free of coronary events of patients with isolated ostial LMCA stenosis did not differ significantly from those of patients with nonostial stenosis (p=0.801, p=0.970, respectively). Conclusion: Postoperative short- and long-term prognosis of isolated LMCA stenosis appears good in terms of mortality and coronary event symptoms.